Effects of chains squat training with different chain load ratio on the explosive strength of young basketball players’ lower limbs - Jiang, Dongting; Xu, Gang (Frontiers in Physiology, 2022)
The purpose of this study was to explore the effects of the chain squat training (CST) with different chain load ratio (0, 10%, 20% and 30%) on the explosive power of the lower limbs of adolescent male basketball players. Forty-four youth basketball players (age 15.48 ± 0.81 years, body mass 78.86 ± 12.04 kg, height 184.95 ± 6.71 cm) were randomly allocated to one of the four groups: traditional squat training (TST), 10% chains squat training (10% CST), 20% chains squat training (20% CST), and 30% chains squat training (30% CST). Training interventions were performed 2 times per week for 6 weeks, and at the week before (Pre) and after (Post) the 6-week CST program with different chain load ratio, the no-step vertical jump, standing long jump, 15 m shuttle run, 1 R M squat and 30 m sprint test were performed. A 4 (group) × 2 (time) repeated measures analysis of variances (ANOVA) was calculated to show the scatter of each variable, and the Bonferroni’s post-hoc test was used for multiple comparisons, in addition the partial eta-squared (η2) was calculated as an estimate of the ES. Significant time × group interaction was noticed for the no-step vertical jump (p < 0.001; η2 = 0.611), standing long jump (p < 0.001; η2 = 0.490) and 1 R M squat (p < 0.01; η2 = 0.333) indicating that better improvements appear in CST compared to TST. However, significant time × group interaction was noted for 15 m shuttle run (p < 0.001; η2 = 0.428), in favor of TST compared to CST. In addition, the improvements in 30 m sprint were similar between all groups. In conclusion, CST with more chain load has better training effects on lower limb explosive strength and maximum strength, based on the improvement in 1 R M squat and jumping performance. Besides, compared with TST, CST with more chain load might not help to develop better velocity adaptation at higher range of movement.